3.6x-1.2=.7(10-x)

Simple and best practice solution for 3.6x-1.2=.7(10-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3.6x-1.2=.7(10-x) equation:


3.6x-1.2=.7(10-x)

We simplify the equation to the form, which is simple to understand
3.6x-1.2=.7(10-x)

Reorder the terms in parentheses
3.6x-1.2=+(+7-0.7x)

Remove unnecessary parentheses
+3.6x-1.2=+7-0.7x

We move all terms containing x to the left and all other terms to the right.
+3.6x + 0.7x=+7+1.2

We simplify left and right side of the equation.
+4.3x=+8.2

We divide both sides of the equation by 4.3 to get x.
x=1.906976744186

See similar equations:

| 6.5(1+0.495x)=5.114+4.3x | | 19694.08=2*3.14*196+2*3.14*14*h | | .3x=1.2+2.3x | | 64d^5-32d^2= | | 6x+1.5=4x-3 | | 0.4(x-10)+0.6x=1 | | Y+(3-5)=12 | | (5z+3)(8+z)=0 | | 7sec(x)=7 | | 33.33t=-.25 | | -16-3c=5c | | 8343.8592=2*3.14*17.64+2*3.14*4.2*h | | -15n+8n+34-4=-65 | | 0.3z-62.1=3z | | -.1a=0 | | 15n+8n+34-4=-65 | | 6x-8x+5=-2x+-4+7 | | 1965.7656=2*3.14*54.76+2*3.14*7.4*h | | 15q+13q+8q=180 | | 3y=5-2y | | 3x+63+66=180 | | 20t+5t+5t=180 | | 3t+69+78=180 | | 1.4t+2.7=5.5 | | -25.294-0.8*-4.6=-3.2+2.7(2.7*-4.6+5.6) | | -8x-3=37 | | -25.294-0.8*4.6=-3.2+2.7(2.7*4.6+5.6) | | .5(x-1)=.33(x+1) | | x=0.5(10x-40) | | 72842.976=2*3.14*1281.64+2*3.14*35.8*h | | 8u-4u=19 | | D=150-10P |

Equations solver categories